A method for reconstructing global ocean-induced surface displacements from land-based in-situ stations. (January 2015) - Kuhlmann, Julian; Rogozhina, Irina; Dill, Robert; Bergmann-Wolf, Inga; Thomas, Maik
Abstract : Highlights: Method for reconstructing a global, time-variable field of crustal displacements caused by non-tidal ocean loading (NTOL) from a small number of local measurements. Decomposition of the NTOL field into empirical orthogonal functions (EOFs) obtained from GRACE satellite data. We achieve the reproduction of a highly correlated displacement signal across 95% of the land surface. Useful complement to existing data sets of ocean mass-induced surface displacement. Abstract: We present a method for reconstructing a global, time-variable field of displacements of the Earth's crust caused by non-tidal ocean loading (NTOL) from a small number of local displacement measurements. This is achieved by the decomposition of the NTOL field into empirical orthogonal functions (EOFs), which we obtain from GRACE satellite data. With this method, we achieve the reproduction of a highly correlated displacement signal across 95% of the land surface and the reduction of residual continental displacement from up to 1 mm to mostly below 0.5 mm on monthly GRACE data. The extrapolation of the displacement signal into the time for which no global EOF patterns can be recovered is exemplarily shown. Further, the possibilities and limitations of applying the method on submonthly GRACE products are investigated. We conclude that the described method can be a useful complement to existing data sets of ocean mass-induced surface displacement, especially when in-situ measurement accuracy has improved.